Translation Motion-Based Backpack for Indonesian Army Soldiers as a Source of Energy for Military Communication Devices - Jerry Barto Naga; Dekki Widiatmoko; Kasiyanto Kasiyanto (Prodi Ilmu Komputer Universitas Bumigora, 2023)
Background: Energy is an aspect that is very necessary in human life, because every activity we do consumes and produces energy. Among various sources of energy, human physical activity is a potential energy source that can be utilized.Objective: This research aims to design a backpack with translation motion as an energy source for military communication devices.Methods: The design of this tool uses the research and development method.Result: The results of the study indicate that walking produces a voltage of approximately 3.863 volts, climbing stairs produces 4.56 volts, and running generates 5.39 volts. The voltage generated increases with the level of human movement involved.Conclusion: In conclusion, the more human movement is involved, the higher the voltage generated. The calculated spring constant is Ktotal = 22.612 N/m, with a unit spring constant of 11.306 N/m. F